The relationship between health literacy and colorectal cancer early diagnosis in the elderly - Elahe Tavassoli; Amin Moazamani; Forouzan Ganji (Payesh)
Objective(s): The level of health literacy is not the same in all people, and the level of health literacy is lower in the group of the elderly, immigrants and people with low economic status. Considering the importance of health literacy and obtaining useful information and performing screening behaviors in the elderly, the present study aimed to assess the relationship between health literacy and performing colorectal cancer early diagnosis in the elderly of Shahrekord, Iran. Methods: This cross-sectional study examined the level of health literacy and performing cancer-screening behaviors in the 351elderly of Shahrekord whose information was fully recorded in electronic case records and selected randomly. After collecting information using standard health literacy questionnaire and checklist about colorectal cancer early diagnosis, the data was analyzed using SPSS version 25 software. Results: The mean age of the elderly participants in the study was 67.08 ± 5.75 years. The mean health literacy score of the elderly was 60.65±12. About 52% of elderly had performed colorectal cancer screening. The mean score of health literacy was higher in men (p<0.001). Married people, self-employed, university educated, the elderly with a history of illness in the family, had higher health literacy (p<0.001). There was a significant relationship between the health literacy score and colorectal cancer early diagnosis (p<0.001). Conclusion: Improving health literacy may be an effective strategy in improving and promoting colorectal cancer early diagnosis in the elderly. Therefore, developing comprehensive programs, creating simple and understandable media and educational materials, as well as effective educational interventions for people with insufficient health literacy can be an effective step to improve health literacy among this population.